The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.21037/cdt.2018.09.07
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary vein remodeling following pulmonary vein isolation in patients with atrial fibrillation—do pulmonary veins represent only an epiphenomenon? A cardiac MRI study

Abstract: Background: After successful pulmonary vein isolation (PVI) for atrial fibrillation (AF), the left atrium (LA) undergoes reverse remodeling. However, few studies have directly studied pulmonary vein (PV) remodeling and focused on whether pre PVI-PV conditions could predict outcome of the procedure. We hypothesize that: (I) post PVI, in addition to LA remodeling the PVs undergo a parallel degree of remodeling; and (II) that PV characteristics pre PVI can be used to identify patients more likely to sustain norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…It is generally known that the reverse remodeling of the LAs occurs after successful PV isolation for AF 3–5 . Khidr et al reported that reduction in PV cross‐sectional areas correlated with the LA volume reduction after PV isolation by RFA and suggested that reverse remodeling of the PVs reflects that of the LA 4 . Similar to this study, the morphological changes in the PVs after CBA should also be analyzed by considering the effect of volume reduction of LA.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…It is generally known that the reverse remodeling of the LAs occurs after successful PV isolation for AF 3–5 . Khidr et al reported that reduction in PV cross‐sectional areas correlated with the LA volume reduction after PV isolation by RFA and suggested that reverse remodeling of the PVs reflects that of the LA 4 . Similar to this study, the morphological changes in the PVs after CBA should also be analyzed by considering the effect of volume reduction of LA.…”
Section: Discussionsupporting
confidence: 63%
“…This may suggest that the postoperative reduction in PV area can be explained by the effect of shrinkage of the LA. It is generally known that the reverse remodeling of the LAs occurs after successful PV isolation for AF 3–5 . Khidr et al reported that reduction in PV cross‐sectional areas correlated with the LA volume reduction after PV isolation by RFA and suggested that reverse remodeling of the PVs reflects that of the LA 4 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this conceptual model, several previous studies have shown reverse structural remodeling following catheter ablation therapy. [7][8][9][10][11][12][13]17 To date, data are limited about remodeling in drug treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…6 Following catheter ablation therapy, decreases in left atrial volume and PV diameters (reverse structural remodeling) have been observed. [7][8][9][10][11][12][13][14][15][16] The clinical consequences of reverse remodeling are not well defined, but some studies have reported that reverse remodeling is associated with decreased AF recurrence 10,12 and improved cardiac function. 10 While reverse remodeling after catheter ablation therapy has been shown in several previous studies, [7][8][9][10][11][12][13]17 none have compared the magnitude of reverse remodeling changes in ablation with an appropriately selected control group of patients treated with drug therapy.…”
mentioning
confidence: 99%